The large carrion beetles (Coleoptera: Silphidae) of Turkey: a review with a new species record - Çi̇ftçi̇ Derya; Růžička, Jan; Hasbenli̇ Abdullah; Şahi̇n Ülfet (Zootaxa, 2018)
A total of 24 species and subspecies of Silphidae (ten belonging to the subfamily Nicrophorinae and 14 to Silphinae) are reported from Turkey. This list combines a literature review with examination of specimens collected in various regions of Turkey, and mostly housed at the Metin Aktaş Zoological Museum of Gazi University, Ankara, Turkey and in the collection of Jan Růžička, Prague, Czech Republic. One species, Silpha olivieri Bedel, 1887, is reported from Turkey for the first time. The occurrence of Nicrophorus sepultor Charpentier, 1825 in Turkey is confirmed, based on abundant recently collected material from north-western Turkey. For several other species, we provide new province records within Turkey. Thanatophilus ferrugatus (Solsky, 1874) is excluded from the Turkish fauna, since the published record was based on misidentification of the similar T. terminatus (Hummel, 1825). We provide a key to adults of species and subspecies known from Turkey, and distribution maps and photographs of all taxa.